Analisis Risiko Keselamatan dan Kesehatan Kerja pada Laboratorium Teknik Sipil Fakultas Teknik Universitas Palangka Raya - Yosepha Sindya Vionita; Subrata Aditama K.A Uda; Veronika Happy Puspasari (Jurnal Serambi Engineering, 2024)
Awareness of potential hazards is very important in order to minimise any risks and losses that may occur when applying the K3 principles in the work environment. One of the work environments that has the potential to cause work accidents and work-related diseases is the laboratory. The Civil Engineering Laboratory of Palangka Raya University does not currently have a K3 management system. It is hoped that this research can help the laboratory managers to create K3 SOPs to prevent the possibility of accidents while performing activities in the laboratory. This research aims to identify hazards, determine the level of risk and plan alternative ways to control risk in the Civil Engineering Laboratory of Palangka Raya University, namely in all practical and research activities by conducting direct observations, interviews and collecting secondary data. This analysis was conducted based on the HIRADC (Hazard Identification, Risk Assessment, and Determining Control) method by identifying hazards, risk assessment, and risk control. The results of the process of hazard identification, risk assessment and planning of alternative risk controls were obtained at the Civil Computing Laboratory, Soil Mechanics Laboratory, Highway Laboratory in the following order: low risk 45.7%, 87%, 47.6% medium risk 11.4%, 13%, 30.9% high risk 42.9%, 0%, 21.5%. By controlling risks based on the risk control hierarchy of elimination, substitution, engineering, administration and personal protective equipment